2015
DOI: 10.1371/journal.pone.0128362
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Enriched Three-Dimensional Matrix Reduces Inflammatory and Catabolic Mediators Production by Human Chondrocytes

Abstract: This in vitro study investigated the metabolism of human osteoarthritic (OA) chondrocytes encapsulated in a spherical matrix enriched of chitosan. Human OA chondrocytes were encapsulated and cultured for 28 days either in chitosan-alginate beads or in alginate beads. The beads were formed by slowly passing dropwise either the chitosan 0.6%–alginate 1.2% or the alginate 1.2% solution through a syringe into a 102 mM CaCl2 solution. Beads were analyzed histologically after 28 days. Interleukin (IL)-6 and -8, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
(41 reference statements)
4
16
0
1
Order By: Relevance
“…In our paper, we found that CS or HA-CS slightly but not significantly decreased NO 2 − , PGE2, and GAG, a finding consistent with previous investigations [27, 28]. The findings of the present study suggested that CS-IL-1Ra and HA-CS-IL-1Ra inhibited the production of inflammatory agents such as NO 2 − and PGE2, while decreasing the degradation of GAG induced by IL-1 β in chondrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In our paper, we found that CS or HA-CS slightly but not significantly decreased NO 2 − , PGE2, and GAG, a finding consistent with previous investigations [27, 28]. The findings of the present study suggested that CS-IL-1Ra and HA-CS-IL-1Ra inhibited the production of inflammatory agents such as NO 2 − and PGE2, while decreasing the degradation of GAG induced by IL-1 β in chondrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…The research of Oprenyeszk et al 42 conrmed that the production of inammatory mediators IL-6 (p ¼ 0.0012), IL-8 (p < 0.0001), and PGE2 (p ¼ 0.0056) by chondrocytes was signicantly reduced by the addition of chitosan aer a 3 day culture. Furthermore, this signicant inhibitory effect was sustained during a culture period of 17-21 days.…”
Section: Bioactivities Of Chitosanmentioning
confidence: 99%
“…Chitosan is one of the most widely investigated polymers for regenerative medicine, in particular for cartilage regeneration because it displays structural properties that are similar to natural glycosaminoglycans . Chitosan promotes the expression of cartilage matrix compounds and reduces production of inflammatory and catabolic mediators by chondrocytes . A chitosan gel has been combined with microfracture to stabilize the blood clot and factors obtained from bone marrow stimulation, resulting in superior cartilage repair compared with microfracture alone up to 5 years postoperatively .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Chitosan promotes the expression of cartilage matrix compounds and reduces production of inflammatory and catabolic mediators by chondrocytes. 21 A chitosan gel has been combined with microfracture to stabilize the blood clot and factors obtained from bone marrow stimulation, resulting in superior cartilage repair compared with microfracture alone up to 5 years postoperatively. 22 Hydroxypropylmethylcellulose (HPMC) provides a suitable environment for autologous stroma cells and chondrocytes 23 and induced cartilage formation with a hyaline-like organization in a rabbit cartilage defect model.…”
Section: Introductionmentioning
confidence: 99%